Locus Of Control Sebagai Penguat Peran Etika Profesi Dan Audit Judgment Dalam Meningkatkan Kredibilitas Akuntan Publik - Mutiara Rachma Ardhiani; Nashrudin Latif (Politeknik Ganesha Medan, 2023)
The purpose of this study was to analyze the influence of professional ethics on the credibility of public accountants through audit judgment moderated by locus of control. The research was conducted on public accountants who worked at 24 KAPs in East Java which were registered in the database of Otoritas Jasa Keuangan (OJK). The data that has been obtained was analyzed quantitatively with path analysis to examine the effect of mediating variables and moderated regression analysis to examine the effect of moderating variables. The results of the study show that Professional Ethics has a direct and indirect effect on the Credibility of Public Accountants through Audit Judgment. Testing with the moderating variable gives two different results. First, Locus of Control can moderate the influence of Professional Ethics on the Credibility of Public Accountants, and secondly, Locus of Control does not moderate the effect of Audit Judgment on the Credibility of Public Accountants